Kinerja Badan Kepegawaian Daerah (BKD) dalam Rekrutimen Calon Pegawai Negeri Sipil di Provinsi Maluku Utara. - Abdullah, Suryadi Said; Tulusan, Femy; Dengo, Salmin (Sam Ratulangi University, 2014)
In Law No. 43 Year 1999 on the Principles of Civil Service in the fourth paragraph states that, the government and the organizers of the smooth implementation of national development mainly depends on the perfection and perfection State apparatus State apparatus is substantially dependent on the Civil Service as a Civil Servant So the State apparatus a decisive factor in determining the success or failure of the government to governance and national development. Recruitment of civil service candidates here are the most urgent are in the process of realizing the state apparatus qualification. BKD in this case has the responsibility to make this happen as stipulated in Presidential Decree No. 159 of 2000 Departing from this, the authors are interested in doing research with title Performance Regional Employment Agency (BKD) in overseas recruitment candidates for Civil Servants in the province of North Maluku. The purpose of this study is to describe, analyze and know how staffing Agency Regional Performance in Recruitment Candidates for Civil Servants (CPNS) in the province of North Maluku. And what constraints in the implementation of Candidates Recruitment of Civil Servants (CPNS) by the Regional Employment Board of North Maluku province, In this study using qualitative analysis methods presented descriptively by using indicators of Holloway, namely accountability, efficiency, effectiveness, and equity (fairness). From the research that has been conducted on the whole the authors concluded that the implementation of the Recruitment of candidates for Civil Servants conducted by the Regional Employment agency of North Maluku Province normative and procedural already been effective, but there is still infrastructure is still lacking fraction indicated. Keywords : Recruitment Candidates Recruitment of Civil Servants